Islamic transformation centre – leveraging on e-baitulmal through the quadruple helix model (QHM) collaboration - Ahmad Dahlan, Abdul Rahman; Mohd Suhaili, Nur Shahirah; Khalid, Khairani; Ismail, Nur Syamimi (Research Publish Journals, 2015)
Economy is a system of collection and distribution of resources. However, loans nowadays imbalances the world economy by making the rich richer and the poor poorer. This paper intends to propose a conceptual solution that provides a holistic development of economy focusing on Zakat, Musharakah, Mudharabah and Baitulmal with “ukhrawi” (or Hereafter) elements. The paper is based on literature review, real world observations and adopting business model canvas (BMC) framework in building a conceptual solution for holistic development of Islamic economy. This paper explores the opportunity of providing holistic and balanced economy to entrepreneur by leveraging the baitulmal just like what the Prophet Muhammad’s صلى الله عليه وسلم used to do during his time, and at the same time generating sustainable revenue and profit utilizing technology-based solution. The findings of this paper show that information system, through the creative use of ICT and Internet, can popularizes baitulmal function to entrepreneurs to build businesses based on sound human values and principles that takes into account the numerous benefits and virtues offered to the human beings, world, and profits.